240 Aetiology and Outcomes of Head and Neck Free Flaps in Patients Aged ≥ 65 Years: The Cambridge Experience. (4th May 2021) - Hjalmarsson, C; Chan, T; Chawla, R; Patel, A
Abstract: Introduction: Elderly patients often present to the Head & Neck Plastic Surgery department with complex reconstructive needs, for which free flaps are the gold-standard management. In order to provide appropriate, patient-centred care, it is imperative to understand how increasing age and related factors affect long-term free flap outcomes. Method: The authors carried out a retrospective review of all patients 65+ years who underwent free flap surgery at Addenbrooke's Hospital from 2008-2019. Patient, operative, and flap characteristics, and outcomes, were analysed using Excel and RStudio. Results: 163 patients were identified (54F, 109M). The majority were ALT (n = 74), radial forearm (n = 35), and fibula flaps (n = 23). Of pre-operative comorbidities, only neurological comorbidities (n = 16), were significantly associated with long-term flap failure (p = 0.016). There was no significant association between number of comorbidities and flap outcome. There was no association between age group and length of stay. Flap site complications, and particularly venous complications, were significantly associated with later failure (p = 0.001). No other complications were statistically associated with flap failure. Conclusions: The high success rate supports the use of free flaps in the 65+ population. This data supports a case-by-case approach to assessing fitness for free flap surgery rather than excluding patients on the basis of age or specific comorbidities.